Tail co-movement in inflation expectations as an indicator of anchoring - Filippo Natoli; Laura Sigalotti (European Central Bank (ECB), 2017)
We analyze the degree of anchoring of inflation expectations in the euro area during the post-crisis period, with a focus on the time span from 2014 onwards when long-term beliefs have substantially drifted away from the policy target. Using a new estimation technique, we look at tail co-movements between short- and long-term distributions of inflation expectations, estimated from daily quotes of inflation derivatives. We find that, during 2014, average correlations between short- and long-term inflation expectations rose sharply; moreover, negative tail events impacting short-term beliefs have been increasingly channeled to long-term views, triggering both downward revisions in expectations and upward changes in uncertainty. Overall, our results signal a risk of downside de-anchoring of long-term inflation expectations.
Keywords: C14; C58; E31; E44; G13; 330; anchoring; inflation expectations; inflation swaps; inflations options; option-implied density; tail co-movement